Prevalence of the Metabolic Syndrome in Psoriasis: Results From the National Health and Nutrition Examination Survey 2003–2006 - Love, Thorvardur Jon (2010)
OBJECTIVE: To estimate the prevalence of the metabolic syndrome among individuals with psoriasis, and to examine the association between these 2 conditions in the general US population. DESIGN: Cross-sectional health survey of a nationally-representative random sample of the noninstitutionalized civilian US population. SETTING: The National Health and Nutrition Examination Survey 2003–2006. PARTICIPANTS: The study included 6549 participants aged 20 to 59 years. MAIN OUTCOME MEASURES: Prevalence of the metabolic syndrome defined by the revised National Cholesterol Education Program Adult Treatment Panel III definition and odds ratios for associations after adjusting for age, sex, race/ethnicity, smoking status, and C-reactive protein levels. RESULTS: The prevalence of the metabolic syndrome was 40% among psoriasis cases and 23% among controls. According to 2008 census data the projected number of patients with psoriasis aged 20 to 59 years with the metabolic syndrome was 2.7 million. The univariate and multivariate odds ratios for patients with psoriasis and the metabolic syndrome were 2.16 (95% confidence interval, 1.16 to 4.03) and 1.96 (1.01 to 3.77), respectively. The most common feature of the metabolic syndrome among patients with psoriasis was abdominal obesity, followed by hypertriglyceridemia and low levels of high density lipoprotein cholesterol. CONCLUSIONS: The prevalence of the metabolic syndrome is high among individuals with psoriasis. Given the serious complications associated with the metabolic syndrome, this frequent comorbidity should be recognized and taken into account in the long-term treatment of individuals with psoriasis.